A legal review on sustainable town planning in Klang Valley: storm water management / Muhammad Hilmi Hassin ... [et al.] - Hassin, Muhammad Hilmi; Azlan, Nur Syazwani; Zainol, Muhammad Nurhadi; Lokman, Siti Norafiqah (2011)
Sustainable Township is one of the key elements in the government's development plan. It has been placed under the category of Environment. The major problem found under the key element of sustainable township is flood mitigation. In the 9th Malaysia Plan, an allocation of RM 4 Billion was allocated for Flood Mitigation project nationwide. In Malaysia we have Manual Saliran Mesra Alam (MASMA) guideline as the main document that provides us with the proper system and mechanism in dealing with Flood Mitigation problem. However, despite the existence of such guidelines, there still exist flood problems and its severity depends on the location of the flood occurrences. With the recent data and information that we gathered, it is found that the MASMA guideline has been facing with some issues which causes problem in its implementation. In this project paper, we shall lay down the problems faced by MASMA and provide the discussion and feedback from the academician and practitioner's point of view. At the end of this project paper we shall provide suggestions and recommendations in order to solve the problems faced by MASMA guidelines.